Women in Colonial Shackles: A Comparative Study of the National Female Figures R.A. Kartini and Choi Yong-Shin - Bae Sangphil; Pujiati Pujiati; Rahimah Rahimah (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This article discusses comparisons from a historical perspective, namely R.A. Kartini as a female character who comes from Indonesia with the female character Choi Yong-shin who comes from Korea. The research results show that the two figures have similarities and differences. Kartini was born into a Javanese aristocratic family, she studied at a European elementary school. After completing her education, Kartini wrote many of her thoughts in the form of letters containing the idea of freedom for Javanese people who had a different social status than hers. Because of her persistence in expressing freedom, Kartini's name was immortalized in Indonesia as a national figure. Choi Yong-shin also received Western education at the American Missionary School in Korea and had the status of a family member. After completing his education, Choi Yong-shin devoted his knowledge to teaching children in Saemgol Village. Choi Yong-shin also had the idea of equality, including that women and men have the same rights and responsibilities to fight for goodness, Choi Yong-shin's name was also immortalized in Korea nationally.